Travailler chez les autres - Colette Le Petitcorps (La Nouvelle Revue du Travail)
France’s “personal services” sector largely involves individuals who work in another person’s home. Drawing on concepts taken from the sociology of gender and domestic work, the paper investigates the complex and dynamic forms used to produce domestic space, based on an empirical study of employees’ relationship to space. It also looks at how different external actors influence the organisation of their working spaces, and at their modes for appropriating these spaces. Questions are asked about the extent to which these spatial practices embody a social relationship that is specific to domestic service and which structures and transforms work relationships in private space.